2020
DOI: 10.1108/bfj-05-2020-0449
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting online food delivery service in Bangladesh: an empirical study

Abstract: PurposeThe core idea of this paper was to empirically evaluate the factors affecting the choices of consumers while ordering food online. The goal was to explore consumer behavior in the emerging industry of online food delivery business in an emerging economy, Bangladesh.Design/methodology/approachThis paper used a qualitative and exploratory approach through the collection and analysis of data from a total of 177 survey respondents. Statistical analyses of all collected data (utilizing t-tests and factor ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
120
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(137 citation statements)
references
References 56 publications
5
120
1
11
Order By: Relevance
“…With the purpose of better reflecting the FDA users’ behaviors, it was decided to include some adaptations of the original model: the need to extend the original UTAUT-2 model with one additional construct, food, and beverage quality. This was essentially because the recent literature has identified that this factor affects both customer satisfaction and behavioral intentions on FDAs services (Annaraud and Berezina, 2020; Saad, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…With the purpose of better reflecting the FDA users’ behaviors, it was decided to include some adaptations of the original model: the need to extend the original UTAUT-2 model with one additional construct, food, and beverage quality. This was essentially because the recent literature has identified that this factor affects both customer satisfaction and behavioral intentions on FDAs services (Annaraud and Berezina, 2020; Saad, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Venkatesh et al , 2012). Thus, the design of an FDA's structure and its ability to process consumer online food orders quickly and efficiently are the most important antecedents of purchase decision (Gunden et al , 2020; Saad, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, scholars have been widely interested in FDS. Several authors have investigated FDSs' role in everyday life, examining the motives and reasons behind their use among people (Saad, 2020), while others have analyzed their impact on restaurant sales (Collins, 2020). However, there are limited investigations available in the FDS segment during the Covid-19 pandemic (Chang and Mayrhoefer, 2020), and research should focus on how technologies and food delivery could restore the entire food services, especially in the European Union (EU-27).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, they estimated at USD66.3 million in 2017 for Malaysian online food delivery market size. The emergence of this phenomena has been recorded in the past studies focusing on online food delivery which frequently stated that by having restaurant come to customer is convenience the (Saad, 2020;Mahfuz, 2019;Hashim et. al.…”
Section: Introductionmentioning
confidence: 98%